Totally geodesic submanifolds in the tangent bundle of a Riemannian 2-manifold - Yampolsky, Alexander (Журнал математичної фізики, аналізу, геометрії, 2005)
We give a full description of totally geodesic submanifolds in the tangent bundle of a Riemannian 2-manifold of constant curvature and present a new class of a cylinder-type totally geodesic submanifolds in the general case. Mathematics Subject Classification: 53B25, 53B20.